The too-good wife : alcohol, codependency, and the politics of nurturance in postwar Japan - Borovoy, Amy Beth (Ethnographic studies in subjectivity, 2005)
Social drinking is an accepted aspect of working life in Japan, and women are left to manage their drunken husbands when the men return home, restoring them to sobriety for the next day of work. In attempting to cope with their husbands' alcoholism, the women face a profound cultural dilemma: when does the nurturing behavior expected of a good wife and mother become part of a pattern of behavior that is actually destructive? How does the celebration of nurturance and dependency mask the exploitative aspects not just of family life but also of public life in Japan?